2017
DOI: 10.4236/wjcmp.2017.74008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cu Ion on the Structural and Optical Properties of Yttrium Doped ZnO by Solution Combustion

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…interstitial sites rather than the sites of Zn 2+ ions, as the 5D 0 → 7F 0 transition is strictly forbidden due to the same total angular momentum . In addition, it has been observed that the intensity corresponding to 5 D 0 → 7 F 2 transition at 612 nm increases as the doping concentration increases and could be attributed to the transfer of energy from ZnO host to Eu 3+ ion …”
Section: Resultsmentioning
confidence: 99%
“…interstitial sites rather than the sites of Zn 2+ ions, as the 5D 0 → 7F 0 transition is strictly forbidden due to the same total angular momentum . In addition, it has been observed that the intensity corresponding to 5 D 0 → 7 F 2 transition at 612 nm increases as the doping concentration increases and could be attributed to the transfer of energy from ZnO host to Eu 3+ ion …”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide (ZnO) is a II-VI semiconductor with wide direct band gap energy (3.37 eV) at room temperature, that is suitable for short wavelength optoelectronic applications and it has a large exciton binding energy (60 meV). Due to its properties like low cost, non-toxicity, abundance in nature, suitability to doping, ZnO has got wide device applications in different areas such as ultraviolet light-emitters, gas sensors, piezoelectric transducers, and solar cells [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this ion is used mainly for its red emission located around 615 nm. This ion is an important candidate for doping ZnO [19][20][21][22][23][24][25][26], due to its possible application in the optoelectronics field, which attracts research groups. Though, the pure and narrow red broadcast could not be obtained, because the latter is always accompanied by a large green emission from the auto-activation centers.…”
Section: Introductionmentioning
confidence: 99%